Response to Heard et al. (1st October 2015) - Moulin, Maryline; Voss, Anne K; Thomas, Tim; Wong, Wendy Wei‐Lynn; Cook, Wendy D; Koentgen, Frank; Vince, James; Silke, John; Vaux, David L
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="embj201592761-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>